Information and Communication Technologies Management and Nigerian Banking Sector Liquidity - Ugoani, John N. N. (2017)
The study sought to explore the relationship between ICTs management and NBS liquidity. ICTs management helps the business to effect proper planning, coordinating, controlling and decision-making. Liquidity is important for banks to meet the demands of customers and a means of public confidence. The Internet connectivity in the NBS discouraged incentives for manipulations and other inefficiencies that characterized the paper and pen banking of the pre-reform era. The e-FASS approach and heavy investments and application of quality ICTs management by banks restored national and international confidence in the NBS which in a great measure, helped to lure back capital and liquidity into the system. Previous studies have found positive relationship between ICTs management and business productivity, bank profitability and economic growth. Through theoretical and empirical results this study found a high positive relationship between ICTs management and NBS liquidity.